Is this Caesarean Really Necessary - Aurangzeb, Muhammad; Hassan, Lubna (Journal of Postgraduate Medical Institute, 2011)
Far too many Caesarean sections are being performed, as fewer doctors achieve the skills of obstetrics and resort more frequently to the ultimate obstetrics answer-the Caesarean section. In an effort to reduce our Caesarean section rate, we undertook a prospective analysis of 97 patients who had previous one or more Caesarean section. 40 patients were unsuitable for a trial of labour. Of the 57 who underwent a trial of labour, only 27 achieve a normal vaginal delivery. Favourable factors leading to a normal vaginal delivery were previous vaginal delivery, particularly after a Caesarean operation, a vertex cephalic presentation and a maternal height of more than 5 feet. The use of Oxytocin and Prostaglandins may reduce the repeat Caesarean section rate.